Radiative forcing and feedback by forests in warm climates – a sensitivity study - U. Port; M. Claussen; V. Brovkin (Earth System Dynamics, 2016)
We evaluate the radiative forcing of forests and the feedbacks triggered by forests in a warm, basically ice-free climate and in a cool climate with permanent high-latitude ice cover using the Max Planck Institute for Meteorology Earth System Model. As a paradigm for a warm climate, we choose the early Eocene, some 54 to 52 million years ago, and for the cool climate, the pre-industrial climate, respectively. To isolate first-order effects, we compare idealised simulations in which all continents are covered either by dense forests or by deserts with either bright or dark soil. In comparison with desert continents covered by bright soil, forested continents warm the planet for the early Eocene climate and for pre-industrial conditions. The warming can be attributed to different feedback processes, though. The lapse-rate and water-vapour feedback is stronger for the early Eocene climate than for the pre-industrial climate, but strong and negative cloud-related feedbacks nearly outweigh the positive lapse-rate and water-vapour feedback for the early Eocene climate. Subsequently, global mean warming by forests is weaker for the early Eocene climate than for pre-industrial conditions. Sea-ice related feedbacks are weak for the almost ice-free climate of the early Eocene, thereby leading to a weaker high-latitude warming by forests than for pre-industrial conditions. When the land is covered with dark soils, and hence, albedo differences between forests and soil are small, forests cool the early Eocene climate more than the pre-industrial climate because the lapse-rate and water-vapour feedbacks are stronger for the early Eocene climate. Cloud-related feedbacks are equally strong in both climates. We conclude that radiative forcing by forests varies little with the climate state, while most subsequent feedbacks depend on the climate state.